Growing carrot year round is lucrative - Kalia, Pritam; Sureja, Amish K.; Saha, Swati (Indian Horticulture, 2019)
The popularity of carrots and their year-round emerging demand led the breeders at Indian Agricultural Research Institute, New Delhi, to develop varieties and hybrids to meet market demand. Their cultivation practices have been standardized. Now, farmers can cultivate them for whole year and can fetch good return.